Media Belajar Sejarah Di Sekolah Menengah Pertama Kelas IX Semester Ganjil - Rahman, Abdul; Destiarini, Destiarini (Jurnal Media Infotama, 2020)
Growing technological advances, special information technology, encourage people to develop media that can be used anytime and anywhere. Apart from that, classical learning methods require teachers to use media that is more relevant to the times, so that students are more motivated to learn history. Media is a learning medium that provides history for Interactive Media. Data collection techniques, which are adapted to the researchers' own needs. Survey analysis is used to verify the necessary data. The objectives of the research are: (a) to create a history of the development of interactive learning media, Interactive Media for class IX students at Odd Semester Middle Schools, (b) to use media-based learning steps for interactive learning media history for class IX students at Odd Semester Middle Schools, (c) to develop materials used in development using Interactive Media for class IX SMP Odd Semester students. The results of history learning media can be applied well in Odd Semester Middle Schools.